1996
DOI: 10.1088/0953-8984/8/12/006
|View full text |Cite
|
Sign up to set email alerts
|

A modified Van der Waals model for the coexistence curve of expanded metals

Abstract: Recent measurements for expanded Hg, Cs and Rb have shown that the liquidvapour coexistence curves for these metals do not obey the 'law of rectilinear diameters'. It is shown here that a two-state Van der Waals equation with a density-dependent cohesive energy will lead to compositional fluctuations that result in a breakdown of the 'law'. Calculations predict that Hg and the alkali metals will exhibit similar behaviour near the critical point. However, in the case of Hg the 6p-6s band-gap closure, which occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
3
8
1
Order By: Relevance
“…In low-density states, a tendency was revealed toward formation of metallic clusters of above-average density, with the distances between these clusters increasing gradually with decreasing average density. This scenario for the behavior of liquid metal in the vicinity of metal-nonmetal transition was suggested by Ross and Hensel [41]. Our data on the distribution of Voronoi polyhedrons agree with this scenario.…”
Section: Discussion Of the Resultssupporting
confidence: 89%
“…In low-density states, a tendency was revealed toward formation of metallic clusters of above-average density, with the distances between these clusters increasing gradually with decreasing average density. This scenario for the behavior of liquid metal in the vicinity of metal-nonmetal transition was suggested by Ross and Hensel [41]. Our data on the distribution of Voronoi polyhedrons agree with this scenario.…”
Section: Discussion Of the Resultssupporting
confidence: 89%
“…For the understanding of the M-NM transition in expanded fluid Hg taking places at a rather large density of 9 g cm À3 , it was pointed out that the density fluctuations near the critical point play an important role [33,34]. By taking fluctuations in the local coordination number into account, Franz [35] showed that a band gap opens at the correct density of 9 g cm À3 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to these liquids, expanded fluid Hg is non-simple. In fact, inhomogeneous regime [11] or two-state model [12] were proposed to explain the electronical and thermodynamic properties of fluid Hg in the M-NM transition region. Fluctuations near the critical point may also play an essential role for the M-NM transition.…”
Section: Introductionmentioning
confidence: 99%